Social dominance orientation and consumer xenocentrism: Mediating role of status consumption and social comparison - Bilal Celik; Aysel Ercis (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This research aims to create a model that elucidates the reasons why people exhibit xenocentric consumer tendencies. In this context, a theoretical framework describing the evolution of consumer xenocentrism (C-XEN) was constructed by integrating elements from diverse theories. Then developed model was analyzed with empirical research involving 534 participants using structural equation modeling (SEM) with AMOS. The findings indicate that individuals with high social dominance orientation are more prone to having C-XEN, and proposes that status consumption and social comparison mediates the relationship between the social dominance orientation and the emergence of C-XEN. The framework allows to grasp the psychological factors contributing to C-XEN. In conclusion, testable propositions that are verifiable are believed to promote additional researches on the matter going forward.
Keywords: 330; Consumer xenocentrism; social dominance orientation; system justification; social comparison; status consumption